Semantics bias in cross-national comparative analyses: is it good or bad to have "fair" health?. Issue 1 (December 2016) - Schnohr, Christina; Gobina, Inese; Santos, Teresa; Mazur, Joanna; Alikasifuglu, Mujgan; Välimaa, Raili; Corell, Maria; Hagquist, Curt; Dalmasso, Paola; Movseyan, Yeva; Cavallo, Franco; van Dorsselaer, Saskia; et al.
Abstract The Health Behavior in School-aged Children is a cross-national study collecting data on social and health indicators on adolescents in 43 countries. The study provides comparable data on health behaviors and health outcomes through the use of a common protocol, which have been a back bone of the study sine its initiation in 1983. Recent years, researchers within the study have noticed a questionable comparability on the widely used item on self-rated health. One of the four response categories to the item "Would you say your health is….?" showed particular variation, as the response category "Fair" varied from 20 % in Latvia and Moldova to 3–4 % in Bulgaria and Macedonia. A qualitative mini-survey of the back-translations showed that the response category "Fair" had a negative slant in 25 countries, a positive slant in 10 countries and was considered neutral in 9 countries. This finding indicates that there are what may be called semantic issues affecting comparability in international studies, since the same original word (in an English original) is interpreted differently across countries and cultures. The paper test and discuss a few possible explanations to this, however, only leaving to future studies to hold a cautious approach to international comparisons if working with the self-rated health item with four response categories.